Innovative cardiovascular primary prevention population-based strategies: a 2-year hybrid type 1 implementation randomised control trial (RCT) which evaluates behavioural change conducted by community champions compared with brief advice only from the SPICES project (scaling-up packages of interventions for cardiovascular disease prevention in selected sites in Europe and sub-Saharan Africa) - Delphine Le Goff; Marie Barais; Gabriel Perraud; Jeremy Derriennic; Paul Aujoulat; Morgane Guillou-Landreat; Jean Yves Le Reste (BMC Public Health, 2021)
Abstract Background Cardiovascular diseases (CVD) caused 17.9 million deaths worldwide in 2016, being the world’s leading cause of death. Prevention of CVD in high-income countries is expensive and fails to reach the population at risk. In low-income countries, it is under-developed. The SPICES project implements a community-based program to improve CVD prevention in 3 European countries and 2 Sub-Saharan countries, based on using community champions to effect behavioural changes. In France, the project operates in “Pays Centre Ouest Bretagne” (COB) which is the Central West Brittany area, and a vulnerable, rural setting. The aim of this study is to assess this innovative prevention strategy versus brief advice. Methods A two-step RCT hybrid type 1 implementation study will first of all screen a population using the Non-Laboratory INTERHEART Score (NL-IHRS) and will involve health-care students at public events in the COB area until 1000 participants have been recruited. Second, a RCT will be carried out. The research team will contact each participant with an intermediate NL-IHRS in order to include them. Participants will be over 18 years of age and work or live in the COB area. Participants will be equally randomised in two groups. The intervention group will receive brief advice plus behavioural change guidance carried out by community champions. The control group will receive brief advice only. The main objective for the RCT is to assess a difference of at least 15% in the NL-IHRS between the two groups after 24 months. The primary outcome will be analysed with intention to treat. Secondary outcomes for the RCT will be assessed using validated questionnaires: the WHOQOL-BREF, the DASH Q questionnaire, the IPAQ-short; smoking level will be assessed according to the NL-IHRS scoring system; a modified self-declared alcohol consumption questionnaire has been developed and gauges will be used to assess BMI. The implementation strategy will use mixed methods: qualitative research methods and quantitative epidemiological studies. Discussion A difference in the mean NL-IHRS of 15% will provide an argument in favour of reorganising prevention policies. A substantial change would favour relocating primary prevention from healthcare professionals to lay people and the community. Trial registration Clinical Trials NCT03886064 - the study was recorded on ClinicalTrials.gov , the 22nd of March 2019.